Rare Variants in Genes Encoding Subunits of the Epithelial Na+ Channel Are Associated With Blood Pressure and Kidney Function. Issue 11 (4th October 2022) - Blobner, Brandon M.; Kirabo, Annet; Kashlan, Ossama B.; Sheng, Shaohu; Arnett, Donna K.; Becker, Lewis C.; Boerwinkle, Eric; Carlson, Jenna C.; Gao, Yan; Gibbs, Richard A.; He, Jiang; Irvin, Marguerite R.; et al.
Abstract : Background: The epithelial Na + channel (ENaC) is intrinsically linked to fluid volume homeostasis and blood pressure. Specific rare mutations in SCNN1A, SCNN1B, and SCNN1G, genes encoding the α, β, and γ subunits of ENaC, respectively, are associated with extreme blood pressure phenotypes. No associations between blood pressure and SCNN1D, which encodes the δ subunit of ENaC, have been reported. A small number of sequence variants in ENaC subunits have been reported to affect functional transport in vitro or blood pressure. The effects of the vast majority of rare and low-frequency ENaC variants on blood pressure are not known. Methods: We explored the association of low frequency and rare variants in the genes encoding ENaC subunits, with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure. Using whole-genome sequencing data from 14 studies participating in the Trans-Omics in Precision Medicine Whole-Genome Sequencing Program, and sequence kernel association tests. Results: We found that variants in SCNN1A and SCNN1B were associated with diastolic blood pressure and mean arterial pressure ( P <0.00625). Although SCNN1D is poorly expressed in human kidney tissue, SCNN1D variants were associated with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure ( P <0.00625). ENaC variants in 2 of the 4 subunits ( SCNN1B and SCNN1D ) were also associated with estimated glomerular filtration rate ( P <0.00625), but not with stroke. Conclusions: Our results suggest that variants in extrarenal ENaCs, in addition to ENaCs expressed in kidneys, influence blood pressure and kidney function.